DrawMyPhoto: Assisting Novices in Drawing from Photographs - Williford, Blake; Pahud, Michel; Hinckley, Ken; Doke, Abhay; Hammond, Tracy (C & C 2019, Proceedings of the 12th conference on Creativity and Cognition, 2019)
We present DrawMyPhoto, an interactive system that can assist a drawing novice in producing a quality drawing by automatically parsing a photograph in to a step-by-step drawing tutorial. The system utilizes image processing to produce distinct line work and shading steps from the photograph, and offers novel real-time feedback on pressure and tilt, along with grip suggestions as the user completes the tutorial. Our evaluation showed that the generated steps and real-time assistance allowed novices to produce significantly better drawings than with a more traditional grid-based approach, particularly with respect to accuracy, shading, and details. This was confirmed by domain experts who blindly rated the drawings. The participants responded well to the real-time feedback, and believed it helped them learn proper shading techniques and the order in which a drawing should be approached. We saw promising potential in the tool to boost the confidence of novices and lower the barrier to artistic creation.